2005
DOI: 10.1603/0022-0493-98.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of the Effects of Planting Date and Application Rate of Imidacloprid for Management of Cereal Aphids and Barley Yellow Dwarf in Winter Wheat

Abstract: The effects of planting date and application rate of imidacloprid for control of Schizaphis graminum Rondani, Rhopalosiphum padi L. (Homoptera: Aphididae), and barley yellow dwarf virus (BYDV) in hard red winter wheat were studied. The first experiment was conducted from 1997 to 1999 at two locations and consisted of three planting dates and four rates of imidacloprid-treated seed. The second experiment was conducted from 2001 to 2002 in Stillwater, OK, and consisted of two varieties of hard red winter wheat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Similarly, studies of the efficacy of imidacloprid dressing of winter wheat in North America suggest that yield benefits are small (compared to unprotected, control crops) and often exceeded by the cost of the pesticide (Royer et al . ). In contrast, in Western Australia, McKirdy, Jones & Nutter () demonstrated that application of an imidacloprid seed dressing to spring wheat is cost‐effective compared to using no pest control, but that using foliar applications of alpha‐cypermethrin (which is much cheaper) provided a significantly higher economic return.…”
Section: Economic Benefits Of Neonicotinoidsmentioning
confidence: 97%
“…Similarly, studies of the efficacy of imidacloprid dressing of winter wheat in North America suggest that yield benefits are small (compared to unprotected, control crops) and often exceeded by the cost of the pesticide (Royer et al . ). In contrast, in Western Australia, McKirdy, Jones & Nutter () demonstrated that application of an imidacloprid seed dressing to spring wheat is cost‐effective compared to using no pest control, but that using foliar applications of alpha‐cypermethrin (which is much cheaper) provided a significantly higher economic return.…”
Section: Economic Benefits Of Neonicotinoidsmentioning
confidence: 97%
“…Perry et al (Perry et al, 2000) found an average of 30% yield loss in affected winter wheat fields. Significant agricultural research efforts are aimed at reducing the impact of the YDVs on the yield of the various crop systems by (i) altering planting time and/or pesticide application regimes to avoid the accumulation of high densities of aphids, (ii) tilling practices, and (iii) developing virus-resistance crop varieties (Chain et al, 2005; Royer et al, 2005; Kennedy and Connery, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For the conditions of the year 2011, the ST and the control treatment without insecticide application showed the best return; however it is important to note that there was a lower aphid population in 2011, and there was no statistical difference between treatments for yield. This same advantage was cited by Royer et al (2005), who mentioned that the ST with insecticide, as imidacloprid for instance, has certain economic and environmental qualities, such as low utilization rates (low doses per target), low exposure to the applicator and the prevention of cultures to virus. In 2011, among all the costs of each treatment, the cost of insecticide (product + application) was equivalent to 13.5% of total expenditures in T1, 6% in T2, and 1% in T3.…”
Section: Resultsmentioning
confidence: 56%